1998
DOI: 10.1088/0022-3727/31/20/030
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the gas temperature in high-pressure microwave discharges in hydrogen

Abstract: Results of experimental determinations of the gas temperature and plasma parameters in a microwave discharge not at thermal equilibrium are presented. The investigation is concerned with high-pressure hydrogen under conditions such that radiation is emitted both by atomic and by molecular components of the plasma are primarily governed by the interaction of the excited atoms and molecules with heavy particles. Because this takes place the approximate models which are successfully applied to analyse data from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Ovtchinnikov et al [5] measured, in a dc discharge, the rotational temperature corresponding to the population densities of the d 3 u substates involved in the emission of the Q-band of the Fülcher system, and showed that this temperature is in good agreement with the translational temperature obtained from the Doppler broadening of Hα and Dα spectral lines. The same conclusions were obtained by Gritsinin et al [6] in a high-pressure hydrogen discharge sustained in a cylindrical chamber using a microwave excitation device. Concerning the use of the rotational temperature of the H 2 (G 1 + g ) state for the determination of the gas temperature, the results are controversial.…”
Section: Introductionsupporting
confidence: 86%
“…Ovtchinnikov et al [5] measured, in a dc discharge, the rotational temperature corresponding to the population densities of the d 3 u substates involved in the emission of the Q-band of the Fülcher system, and showed that this temperature is in good agreement with the translational temperature obtained from the Doppler broadening of Hα and Dα spectral lines. The same conclusions were obtained by Gritsinin et al [6] in a high-pressure hydrogen discharge sustained in a cylindrical chamber using a microwave excitation device. Concerning the use of the rotational temperature of the H 2 (G 1 + g ) state for the determination of the gas temperature, the results are controversial.…”
Section: Introductionsupporting
confidence: 86%
“…H 2 shows a wealth of rovibrational structures in the visible and near-infrared (IR) spectral regions associated with transitions between bound excited electronic states. Most prior experimental studies of MW-activated hydrogen-containing plasmas have focused on the d 3 Π u –a 3 Σ g + (Fulcher) system, , though lines within the G 1 Σ g + –B 1 Σ u + origin band and a 3 Σ g + –b 3 Σ u + continuum emission , have been used for plasma diagnostics, and limited studies have been undertaken using the e 3 Σ u + –a 3 Σ g + system . As Figure shows, the structured emissions are from excited states that lie at energies > 13 eV above the ground (X 1 Σ g + ) state of H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The studies reported in [207,[214][215][216] were devoted to developing models that describe the kinetics of collisionalradiative processes involving excited neutral atoms and ions of a hydrogen plasma. The dependence of the rate of neutralization of atomic ions H − and H + (processes 36.0, 41.0, and 41.1) on the electron concentration N e and temperature T e in the nearcathode layer, where negative hydrogenatom ions H − are dominant (N = 10 16 cm −3 ; in the nearelectrode layer, T e ⩾ 1.5 eV, N e = 10 12 -10 14 cm −3 , and H − = 10 11 -10 12 cm −3 ), was theor etically analyzed in [207].…”
Section: Nomentioning
confidence: 99%
“…A model is developed in [216] to describe the excitation of electron states of hydrogen atoms in the flow of recombin ing hydrogen plasma. In contrast to models known in the lit erature, this model takes into account inelastic interactions of excited atoms with heavy particles.…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation